Medwave’S Editorial History, Policies and Guidelines: 4. Author Instructions and Journal Guidelines [Historia, Política y Normas de Medwave: 4. Instrucciones y Directrices Para Autores] - Bachelet-Norelli, V (2017)
This article is the last of a series of four editorials that report on Medwave’s policies, including section policies, formal requisites according to article type, and guidelines for reviewers and authors, with special emphasis on publication and research ethics. The journal believes that it is important to publish its policies in the format of editorials in order to facilitate and ensure dissemination to our broader readership. This editorial focuses on author instructions and again touches upon publication ethics.Este artículo corresponde al último de una serie de cuatro editoriales que reportan acerca de las políticas de Medwave, incluyendo las políticas de secciones, los aspectos formales según tipo de trabajo y las orientaciones generales para autores y revisores, poniendo especial énfasis en la ética de las publicaciones y de la investigación. La revista considera que es importante publicar sus políticas como editoriales para asegurar su debida difusión entre nuestros lectores. El presente editorial habla acerca las instrucciones para autores, y nuevamente aborda aspectos éticas de las publicaciones, además de instruir acerca de los aspectos formales y de formato.